The teaching excursion, a way to promote the study of the locality from the Geography of Cuba - Pérez , Luis Alfonso; Domínguez Pacheco , Danay; Despaigne Revé , Anny Fredy (Revista Minerva, 2022)
For the great pedagogical value that the teaching excursion presents, for the contributions of love and care to nature, for the level of sensitivity assumed in the face of different environmental situations and in the face of the problems of how to contribute to the study of the locality in students of the Geography Career at the University of Cienfuegos, this research is carried out with the aim of designing and implementing a proposal for teaching excursions to strengthen the study of the locality in students. It consists of a summary, introduction, development where the proposal, the proposal, conclusions, and the bibliography are based. It was started from the initial verification and with the application of different diagnostic instruments, on an intentional basis, which allowed us to search for the history of the problem and confirm it.